Physico-chemical characteristics and fatty acid profile of Baillonella toxisperma Pierre traditionally extracted edible oil from Cameroon forests - Fungo, R.; Ngondi, J.J.; Muyonga, John H.; Tchatat, M.; Odjo, S.; Tieguhong, J.C. (African Journal of Food, Agriculture, Nutrition and Development, 2017)
Baillonella toxisperma Pierre oil is an edible oil obtained from the seeds of wildly growing timber producing B. toxisperma tree species in Cameroon and the rest of the Congo Basin forests of West and Central Africa. This oil can be an important source of fat that can be used as a source of food to humans and/or a source of raw materials in the cosmetics, pharmaceutical and nutraceutical industries, to produce important commercial products. In the present study, samples of the seeds of B. toxisperma were harvested from three representative villages, each from the site in South and East of Cameroon. Seed oil was extracted using the traditional extraction method of B. toxisperma oils in rural Cameroon. Physico-chemical characteristics including colour, refractive index, viscosity, oil yield, acid value, peroxide value, saponification value, iodine value and α-tocopherols and fatty acid composition of crude oil of B. toxisperma nuts were all investigated. The oil yields from these seeds ranged from 38.2% to 45.6%. The peroxide, saponification and iodine values ranged from 2.13 to 2.69mEq/kg, 182.13 to 188.30 mg KOH/g and 54.41 to 57.98 I2g/100g, respectively. The highest acid value and α- tocopherols were 14.87 mg KOH/g and 24.3 mg/100g, respectively. The main fatty acids of Baillonella toxisperma Pierre oils were oleic, stearic and palmitic acids. Linoleic acid contents varied between 58.6% and 56.97%. The ratio of unsaturated to saturated fatty acids content in these oils was 2:1. The fact that the physico-chemical characteristics and fatty acid profile are comparable to common vegetable oils shows that the B. toxisperma oil of the researched species from Cameroon is a potential source of valuable oil which might be used for edible, cosmetic, pharmaceutical and other industrial applications. This characterization is a bench mark for monitoring the quality of Baillonella toxisperma Pierre oil, from Cameroon and can be used to enhance its local and international trade.